1982
DOI: 10.1073/pnas.79.8.2460
|View full text |Cite
|
Sign up to set email alerts
|

Methylation at D-aspartyl residues in erythrocytes: possible step in the repair of aged membrane proteins.

Abstract: Reversibly methylated aspartyl residues in human erythrocyte membrane proteins are shown to be in the "unnatural" D configuration. This is demonstrated by treatment of proteolytically derived aspartic acid fi-[3H]methyl ester with Land D-amino-acid oxidases and by the resolution ofdiastereomeric L-leucyl dipeptides containing either L-or D-aspartic acid j3-methyl ester by ion-exchange chromatography. Based on this observation, we propose a novel role for eukaryotic protein carboxyl methyltransferases (protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
86
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(89 citation statements)
references
References 27 publications
3
86
0
Order By: Relevance
“…The hypothesis that damaged as partyl and asparaginyl residues might be subject to repair has arisen from the discov ery of an enzyme that transfers a methyl group from the biological methyl donor S-adenosyl-Z.-methionine to the carboxyl group of L-isoaspartyl and D-aspartyl resi dues, but not to normal L-aspartyl residues [McFadden and Clarke, 1982;Aswad, 1984;Murray and Clarke, 1984;Clarke, 1985], This methyltransferase activity has been found in a variety of cell types, including bac teria, plants, and many mammalian tissues [Clarke, 1985;O'Connor, 1987], but prior to 1981, little was known about its substrate specificity or function. This is because al though it can methylate nearly all cellular proteins in vivo and a number of additional proteins in vitro, only a small fraction of each protein species is actually methylated at any one time.…”
Section: Potential Repair Of Damaged Aspartyl Residuesmentioning
confidence: 99%
See 1 more Smart Citation
“…The hypothesis that damaged as partyl and asparaginyl residues might be subject to repair has arisen from the discov ery of an enzyme that transfers a methyl group from the biological methyl donor S-adenosyl-Z.-methionine to the carboxyl group of L-isoaspartyl and D-aspartyl resi dues, but not to normal L-aspartyl residues [McFadden and Clarke, 1982;Aswad, 1984;Murray and Clarke, 1984;Clarke, 1985], This methyltransferase activity has been found in a variety of cell types, including bac teria, plants, and many mammalian tissues [Clarke, 1985;O'Connor, 1987], but prior to 1981, little was known about its substrate specificity or function. This is because al though it can methylate nearly all cellular proteins in vivo and a number of additional proteins in vitro, only a small fraction of each protein species is actually methylated at any one time.…”
Section: Potential Repair Of Damaged Aspartyl Residuesmentioning
confidence: 99%
“…The first clue to the function of this methyltransferase came when erythrocyte membrane proteins modified in situ with radiolabelled methyl groups were digested with the protease car boxypeptidase Y (CPY). It was found that at least 20% of the radiolabel in the digest was in /)-aspartyl-P-methyl ester, the rest being in methanol and undigested material, suggest ing that £)-aspartyl residues were a major site of méthylation in vivo [McFadden and Clarke, 1982;Lowenson and Clarke, unpubl. results].…”
Section: Potential Repair Of Damaged Aspartyl Residuesmentioning
confidence: 99%
“…Recently, D-Asp was found in the lenses, 1-4 teeth, 5 bones, 6 brains, 7 skin, 8 aortas, 9 erythrocytes, 10 lungs, 11 and ligaments 12 of elderly donors. The presence of D-Asp in aged tissues of the living body is considered the result of racemization of L-Asp in proteins in such metabolically inert tissues.…”
mentioning
confidence: 99%
“…This intermediate ring can hydrolyze at either of its two carbonyl groups, yielding both isoaspartyl (isomerization) and normal aspartyl residues (McFadden and C larke, 1987). The methyltransferase activity has been widely detected in various organisms, which transfer the methyl residue to the side chain carboxyl group of L-isoaspartyl and D-aspartyl residues but not to normal L-aspartyl residues (McFadden and C larke, 1982;Aswad, 1984;Clarke, 1985;Ingrosso et al, 1989), and has been designated protein L-isoaspartyl methyltransferase (PIMT) (C larke, 1985). Experiments performed in vitro have demonstrated that the incubation of synthetic L-isoaspartyl-containing peptides with PIMT results in the conversion of at least 50% of the peptide to the normal L-aspartyl-containing form (Johnson et al, 1987;McFadden and Clarke, 1987).…”
mentioning
confidence: 99%